Stone Relics at the site of Arab Campit - عبد الله الزيدي كاظم; داخل فليح الحسيني نور (Al-Adab Journal, 2018)
The stones are one of the first materials used by Mesopotamia since the Stone Age after its descent from the caves from prehistoric times to the area of ​​the plain and its transition from the stage of collecting the oil to its production. The stones were mentioned in the Sumerian cuneiform sources (Na4) as a pre-stone While mentioned in the Akkadian language as (abnu) as a sign on the stones also. It was adopted by the industry machinery and tools in prehistoric times on the stones in the first place, which led researchers to call the earliest ages by the name of the stone ages for the use of stone as a basic tool in the manufacture of various machines and tools. One of the first tools made by man of stones are axes and sickles The old Iraqis believed that some stones possessed the properties and ability to treat certain diseases that afflict humans, or to pay harm to them or to damage them, as well as to the destruction of grain and other household utensils such as straws and pots. Man of good luck to the person, so they also worked various forms and seals used as mummies in the rituals, as some medical texts described some stones of a certain color and type of magical use in special rituals of healing and quarantine to expel the evil spirits also . The stones were available in the north Mesopotamia many because of the rich mountains of different types of stones in contrast to the central and southern regions of Mesopotamia, where the stone was used on a small scale for the lack of stones in it, so used milk and the wage instead of , However, the scarcity of these stones did not stand a difficult obstacle to use in different industries That was This is why the people of Mesopotamia became known for their trade and trade relations with various countries to import stone types. It was directly with the countries producing the stones and through the countries of its mediator .